New millennium fibers - Hongū, Tatsuya, 1929- (Woodhead : in association with the Textile Institute ; CRC, 2005)
Looking forward to the future it is clear that today's narrow concept of fiber as a basic element for textiles, ropes and nets will become an outmoded notion. The emphasis will instead shift to new and exciting developments in fiber technology and their applications, exploring such fields as biomimetics, nanotechnology and biodegradability. New millennium fibers describes and identifies the scope of high-tech fibers. The present status and prospects of the fiber/textile technology are discussed and the high performance fibers are reviewed from origin to future applications, including carbon fiber. The themes of the book are summarised with a discussion on health care and the environment. As the 21st century progresses fibers will enter into more novel and unexpected applications. We are approaching the age of the wearable computer and organic electroluminescence wearable displays. New potential is open in the fields of car and aerospace industry, civil engineering, separation membranes using hollow fibers for artificial organs, biodegradable fiber for ecological conservation and fibers with biological functions. New millennium fibers explores the exciting roles that fibers will play in the future and will be an essential book for all of those in the textile and fashion industry involved in fiber development or use. Keep up to date with the advances in fiber scienceExplores new and exciting developments in fiber technologyIncludes applications of new millennium fibers.
Keywords: Textile fibers.; elektronické knihy; electronic books